Pengaruh Content Marketing, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian: Studi pada Produk Dessert Box Bittersweet by Najla di Kota Denpasar - Ni Made Adelia Putri Diandra; Gede Bayu Rahanatha (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Najla Farid Bisyir, who created a dessert box business called Bittersweet by Najla, took advantage of the huge opportunities in the food and beverage industry in Indonesia. The popularity of culinary dessert boxes has made many small businesses start their business by selling dessert box products via social media, which means Bittersweet by Najla has many competitors. Apart from that, there are several consumer complaints regarding the price and quality of products expressed through e-commerce. Bittersweet by Najla's content marketing was also complained about because it was considered excessive and not in accordance with reality. This research aims to test and explain the influence of content marketing, price and product quality on purchasing decisions for Bittersweet by Najla consumers. This research was conducted in Denpasar City in June 2024. Data was collected using an instrument in the form of a questionnaire from 105 Bittersweet by Najla consumers who were determined based on a purposive sampling technique. The data obtained was then analyzed using multiple linear regression analysis. The research results show that all hypotheses are supported, namely content marketing has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and product quality has a positive and significant effect on purchasing decisions. The implication of this research is that the better the content marketing, price and product quality, the greater the purchasing decisions.